Henri Mercier and the American Civil War - Carroll, Daniel B., 1928- (Book collections on Project MUSE., 1971)
As French ambassador to the United States from July 1860 through December 1863, Henri Mercier was in an excellent position to observe, report, and influence the events of those crucial years. Through a description of Mercier's diplomacy, Professor Carroll gives a new account of the Civil War-the tenacious nationalism of the Lincoln-Seward government, the French economic distress caused by the loss of the cotton trade, the continental perspective on the War, the men and society of Washington and Richmond. He shows, in particular, that while maintaining friendly relations in Washington, Mercier.